2017
DOI: 10.1515/jvetres-2017-0047
|View full text |Cite
|
Sign up to set email alerts
|

DON-induced changes in bone homeostasis in mink dams

Abstract: IntroductionThe aim of the study was to investigate the mechanical and geometric properties as well as bone tissue and mineral density of long bones in mink dams exposed to deoxynivalenol (DON) since one day after mating, throughout gestation (ca. 46 d) and lactation to pelt harvesting.Material and MethodsThirty clinically healthy multiparous minks (Neovison vison) of the standard dark brown type were used. After the mating, the minks were randomly assigned into two equal groups: non-treated control group and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
0
7
1
1
Order By: Relevance
“…Previous results also indicate that FBs affect cell proliferation in the growth plate, as well as the synthesis of proteoglycans in articular cartilage [10,56]. A previous study performed on minks intoxicated with deoxynivalenol has shown that mycotoxins do not alter bone mineral density, but they do shorten bone and intensify the process of endosteal resorption, leading to a thinner bone wall [33,34].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous results also indicate that FBs affect cell proliferation in the growth plate, as well as the synthesis of proteoglycans in articular cartilage [10,56]. A previous study performed on minks intoxicated with deoxynivalenol has shown that mycotoxins do not alter bone mineral density, but they do shorten bone and intensify the process of endosteal resorption, leading to a thinner bone wall [33,34].…”
Section: Discussionmentioning
confidence: 95%
“…[30][31][32]. Animal studies have highlighted various other effects of mycotoxins including intensified endosteal resorption, thinning of the bone wall and overall weakening of the whole bone [33,34]. However, no previous studies have looked at the effects of prenatal FB exposure on the development of the skeletal system.…”
Section: Discussionmentioning
confidence: 99%
“…Collagen present in skin tissue is mainly collagen type I: 75%, type III: 22%, and type V: 3%, so the collagen type I to type III ratio is about 2.5 [33,34]. In our previous works, in which we examined the effect of DON and bentonite on bone mechanical properties in minks, we suggested that malnutrition resulting from the presence of mycotoxicosis in the diet could impaired synthesis of collagen type I [35,36]. Moreover, the effect of mycotoxins (DON, Ochratoxin A) on collagen synthesis was previously observed in studies performed cell lines, showing that mycotoxins can influence the expression of fibrous collagens, including collagen type III [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Bone tissue density (BTD) for a 5-cm-long mid-diaphyseal part was performed using an AccuPyc 1330 helium pycnometer (Micromeritics, Inc., Norcross, GA, USA). Before analysis, the samples were first defatted in 2:1 chloroform and methanol mixture for 12 h and then heated in an oven at 105 °C for 24 h to remove bound water and cooled at 25 °C in vacuum desiccators [ 26 ].…”
Section: Methodsmentioning
confidence: 99%